Patterns of Integration: Low Educated People and their Jobs in Norway, Italy and Hungary - János Köllő (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
The paper looks at how the distribution of jobs by complexity and firms' willingness to hire low educated labor for jobs of different complexity contribute to unskilled employment in Norway, Italy and Hungary. In search of how unqualified workers can attend complex jobs, it compares their involvement in various forms of post-school skills formation. The countries are also compared by the weight of small firms, which are assumed to assist low skilled workers through interpersonal relationships. The data suggest that unskilled employment in Norway benefits from synergies between work in skill-intensive jobs, intense adult training, informal learning and involvement in civil activities. In Italy, workplaces requiring no literacy skills at all have the largest contribution but small businesses tend to employ low educated workers at a large scale even in highly complex jobs. In Hungary, insufficient skills (relative to Norway) and an undersized small-firm sector (relative to Italy) set limits to the inclusion of the low educated. An extreme degree of social isolation is likely to deteriorate their skills and jobs prospects further.
Keywords: J21; J24; 330; skills; skill requirements; unemployment; firm size